Geographical Distribution Of Agricultural Industries In Wasit Governorate For The Year 2023 (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify the geographical distribution of agricultural industries in Wasit Governorate for the year 2023 at the district level and by type and size of industry, number of workers, size of industry and production quantities.The research found that there was a discrepancy between the administrative units with regard to the number of industrial branches in each district, if the largest number of these branches was recorded in the governorate center in Kut, which numbered (220) industrial establishments, followed by the Aziziya district with (68), then the district of Al-Hay and Al-Suwayra district with (41). An industrial facility for each of them, followed by Al Numaniyah District with (39) industrial facilities, and then Badra District with (15) industrial facilities.